Алгебра, вопрос задал Nebo , 9 лет назад

3 sin^2 x-3sinx cosx -4 cos^2 x= -2

Ответы на вопрос

Ответил chamomile03
0
3sin^2x-3sinxcosx-4cos^2x=-2 \ 3sin^2x-3sinxcosx-4cos^2x+2(cos^2x+sin^2x)=0 \ 3sin^2x-3sinxcosx-4cos^2x+2cos^2x+2sin^2x=0 \ 5sin^2x-3sinxcosx-2cos^2x=0|:cos^2x neq 0 \ 5tg^2x-3tgx-2=0

Замена: tgx=a

5a^2-3a-2=0 \ D=9+4*5*2=49 \ a_1= frac{3+7}{10}=1  \ a_1= frac{3-7}{10}= frac{-4}{10}=-0.4

tgx=1                   или    tgx=-0.4
x= frac{ pi }{4}+ pi k, k∈Z     или  x=arctg(-0.4)+ pi n, n∈Z
                                           x=-arctg0.4+ pi n, n∈Z
Новые вопросы
Математика, 9 лет назад